EFEKTIVITAS KAMPANYE ANTI KANTONG PLASTIK DI SUPERMARKET DALAM MENYOKONG KONSEP KEBERLANJUTAN - Daniel Susilo (UNIVERSITAS PAKUAN, 2023)
The study at hand investigates the efficacy of anti-plastic bag initiatives implemented in supermarkets and their contribution towards the promotion of sustainability. The issue that has been highlighted pertains to a deficiency in comprehending the concrete consequences of these endeavours. The primary aim of this study is to assess the efficacy of the campaign and ascertain potential techniques for promoting sustainable consumer behaviour, utilising the findings as a basis for further enhancement. In order to accomplish this objective, a research approach is employed which entails conducting surveys among a sample of 400 customers of supermarkets, followed by a comprehensive analysis of the collected data. The results suggest a notable decrease in the utilisation of plastic bags as a consequence of the campaign, hence illustrating its efficacy. This study not only emphasises the significance of these initiatives in promoting sustainability but also offers significant information for future policies targeting the promotion of sustainable consumption. This statement implies that effectively implemented marketing initiatives can significantly influence consumer behaviour and make a meaningful contribution towards achieving sustainability goals. The findings of this study have significant ramifications, indicating the possibility of implementing such programmes in several domains of consumer behaviour. This study serves as a foundation for further investigations into successfully implementing sustainable practises across diverse sectors.